Characteristics of elite open-water swimmers - van Heest, J. L.; Mahoney, C. E.; Herr, L. (The Journal of Strength and Conditioning Research, 2004)
Open-water swimming (5, 10, and 25 km) has many unique challenges that separate it from other endurance sports, like marathon running and cycling. The characteristics of a successful open-water swimmer are unclear. The purpose of this study was to determine the physical and metabolic characteristics of a group of elite-level open-water swimmers. The open-water swimmers were participating in a 1-week training camp. Anthropometric, metabolic, and blood chemistry assessments were performed on the athletes. The swimmers had a O2peak of 5.51 ± 0.96 and 5.06 ± 0.57 ml·kg-1·min-1 for males and females, respectively. Their lactate threshold (LT) occurred at a pace equal to 88.75% of peak pace for males and 93.75% for females. These elite open-water swimmers were smaller and lighter than competitive pool swimmers. They possess aerobic metabolic alterations that resulted in enhanced performance in distance swimming. Trainers and coaches should develop dry-land programs that will improve the athlete's muscular endurance. Furthermore, programs should be designed to increase the LT velocity as a percentage of peak swimming velocity.